Exploring the Dimensions Using Exploratory Factor Analysis of Disruptive Factors and Inventory Control - Hashmi, Aamir Rashid; Amirah, Noor Aina; Yusof, Yusnita; Zaliha, Tengku Noor (The Economics and Finance Letters, 2020)
Healthcare industry is directly linked with human lives and face plaguing problems. Therefore, healthcare facilities minimize risks associated with deficiency of medicines or equipment. This study was carried out to find the dimensions of disruptive factors affecting inventory control at public healthcare facilities. From different healthcare facilities of District Sahiwal and Pakpattan 100 respondents were selected by utilizing random sampling. Then, Exploratory Factor Analysis was done in accordance to congregate the study objectives with a structured questionnaire. The results of this study determined two dimensions for each construct. Lastly, a test of reliability was conducted to find the acceptance level. This study broadens the scope of inventory control to healthcare. However, the study was geographically limited and thus, should be extended to other regions as well. Further, for sustainable performance, the study results should act as an enlightening figure for government and especially the healthcare facilitators in the identification of problems.